“Bundatangguh.com” konsep pemberdayaan masyarakat melalui sistem kemitraan bisnis Islam berbasis mompreneur di Madura - Djodi, Wahyu Setiawan; Permata, Arif Rachman Eka; Manara, Ajeng Sonial (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
Facts show that most fishermen's wives only work as housewives and thus do not earn any income. The condition of fishermen's income is uncertain, so fishermen's wives can help their husbands to improve the family's economic needs by working. This has the potential to be developed where the empowerment of homemakers can help improve family welfare. Bundatangguh.com is a website created for community empowerment based on Mompreneur, namely the role of housewives in building their businesses. This research uses a qualitative approach with a phenomenological paradigm. Data collection methods are semi-structured interviews and documentation: data analysis, namely data reduction, data display, and conclusion drawing/verification, case studies. The results of this study indicate that homemakers also have the potential and ability to support the family economy. This potential needs to be utilized by empowering homemakers to become mompreneurs later. This can be achieved by implementing the program on the website